(untitled) (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: The Nyurbinskaya placer is a unique, buried, proximal transport diamond deposit in the Nakyn kimberlite field (NKP) of the Siberian platform. The lower deposits of the placer are deposits of the Dyakhtar stratum, which are characterised by an uneven distribution of kimberlite minerals. In order to identify the patterns of diamond distribution in sedimentary deposits, the features of crystals from the Dyakhtar stratum were studied and the changes in their properties with distance from the Nyurbinskaya kimberlite pipe were analysed. Methodology: The research results are based on the complex mineralogical and optical spectroscopic characteristics of more than 2,000 crystals from the Dyakhtar stratum of the Nyurbinskaya placer with a diamonds size of 8 to 0.25 mm. In addition to the particle size characteristics, 13 physiographic parameters were determined for each crystal and the infra-red absorption integral spectra were obtained. Furthermore, the concentrations of C-, A-, B1-, B2-defects, the averaged values of nitrogen concentrations in certain forms, and the hydrogen concentrations were calculated. The statistical distributions of diamonds for certain parameters were constructed. Results and discussion: Crystals from the deposits of the Dyakhtar stratum are characterized by features typical of the NKP as a whole. An average increase in the fraction of crystals of class -1.5 mm is observed in the deposits of the Dyakhtar stratum compared to the upper horizons of the Nyurbinskaya and Botuobinskaya pipes. Among the sediments of the Dyakhtar stratum are more common crystals with green pigmentation spots and of a sea-green colour. The analysis of the distribution of diamond properties in the Dyakhtar stratum showed the absence of a systematic change in diamond properties with distance from the Nyurbinskaya pipe. Even in the placer area within quarry of the Nyurbinskaya pipe and next to it there is an admixture of crystals that are more characteristic of NKP dykelets. The diamonds from one of the sites of the placer that are remote from the Nyurbinskaya pipe are closer to the Botuobinskaya pipe in terms of the aggregate of their parameters. Conclusion: Within the Nyurbinskaya placer, zoning is observed in the diamond properties in sediments of the Dyakhtar stratum. The differences in individual sections of the placer are most likely due to the structural features of the placer subterrane and the concentration of material from different kimberlite pipes and bodies rather than to the sorting of crystals during sedimentation. The obtained results are important for solving issues of local forecasting of new primary sources in the studied area.